Chimerism 47,XY, + 8/46,XX: Follow-up for 11 Years - de Carvalho, Acácia Fernandes Lacerda; Pitanga, Paula Monique Leite; Alves, Esmeralda Santos; Miguel, Diego Santana Chaves Geraldo; Santo, Laila Damasceno Espirito; de Araújo, Ana Eliete Fernandes; Ornellas, Ana Carolina Pereira; Toralles, Maria Betânia Pereira (Journal of Pediatric Genetics, 2020)
Approximately 30 sex chromosome discordant chimera cases have been reported to date. In particular, there are few reported cases of chimerism involving coexisting normal and abnormal lineages that each carries a distinct sex chromosome complement. To our knowledge, this is the first case of sexual chimerism with a simultaneous chromosomal aneuploidy involving chromosome 8. This report represents the data from 11 years of follow-up.
Keywords: chimerism; hypochromic macules; disorders of sex development; trisomy 8 mosaic; cytogenetics